2013
DOI: 10.3103/s1066369x13050010
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of differentiation operator in the space L 2 on semiaxis

Abstract: Abstract-We establish an upper bound for the error of the best approximation of the first order differentiation operator by linear bounded operators on the set of twice differentiable functions in the space L 2 on the half-line. This upper bound is close to a known lower bound and improves the previously known upper bound due to E. E. Berdysheva. We use a specific operator that is introduced and studied in the paper. DOI: 10.3103/S1066369X13050010Keywords and phrases: Stechkin problem, optimal recovery, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Problem (3.1) was fully solved only in 2014 by Arestov and the second named author [3] . Namely, they showed that…”
Section: The Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Problem (3.1) was fully solved only in 2014 by Arestov and the second named author [3] . Namely, they showed that…”
Section: The Main Resultsmentioning
confidence: 99%
“…Integrating by parts and taking into account that lim t→∞ y(t) = 0, we obtain (see [3] for details) that…”
Section: The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation